2007
DOI: 10.1590/s0100-67622007000200018
|View full text |Cite
|
Sign up to set email alerts
|

Valoração ambiental de áreas de preservação permanente da microbacia do ribeirão São Bartolomeu no Município de Viçosa, MG

Abstract: RESUMO -O objetivo deste trabalho foi estimar o valor monetário das áreas de preservação permanente da microbacia do ribeirão São Bartolomeu, localizada no Município de Viçosa, Minas Gerais. Utilizou-se o Método de Valoração Contingente para estimar a verdadeira disposição a pagar (DAPv) da população de Viçosa pela recuperação ou preservação dessas áreas. A DAPv mensal foi estimada em R$27,98 por domicílio, que resulta, considerando-se a cidade de Viçosa, o montante anual de R$3.863.926,08 para o bem ambiental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
27

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 3 publications
1
10
0
27
Order By: Relevance
“…Several studies have shown that people entrust to the government the obligation to encourage and promote conservation (Mattos et al 2007;Monteiro et al 2012). Governmental responsibility to promote environmental preservation was also the main reason for the unwillingness to pay found in the present study.…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…Several studies have shown that people entrust to the government the obligation to encourage and promote conservation (Mattos et al 2007;Monteiro et al 2012). Governmental responsibility to promote environmental preservation was also the main reason for the unwillingness to pay found in the present study.…”
Section: Resultssupporting
confidence: 43%
“…Governmental responsibility to promote environmental preservation was also the main reason for the unwillingness to pay found in the present study. As suggested by Mattos et al (2007), dissatisfaction with the government may prompt a form of protest through unwillingness to pay. Among our respondents, this form of protest was confirmed by several respondents who reported dissatisfaction with the performance of governmental agencies regarding environmental protection, conservation incentives, and raising of public awareness.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have also used the method to value environmental assets in Brazil. For example, Mattos et al (2007) assessed the Permanent Preservation Area in the Ribeirão São Bartolomeu watershed and reported an average WTP of R$ 27.98 per month among respondents. Fonseca and Drummond (2003) reported that a sample of local residents would be willing to pay approximately R$ 12.53 per month for the conservation of Laguna de Itaipu, in Niterói, RJ.…”
Section: Socioeconomic Profi Le Of Respondents and Their Willingness mentioning
confidence: 99%
“…Indirect use refers to the indirect ownership of a certain resource, such as the appreciation of the landscape's beauty. Non-use value, also known as intrinsic value or existence value, refers to the personal satisfaction generated by a resource, regardless of its present use or the possibility of its future use (Motta 2006;Mattos et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The financial compensation for rural producers and the free or subsidized supply of technical support and inputs to restore these ecosystems can lead to the resumption of their natural functioning and the provision of environmental services provided by these areas (Mattos et al, 2007).…”
Section: /11mentioning
confidence: 99%